Analisis Efektivitas Jalur-Jalur Transmisi Kebijakan Moneter dengan Sasaran Tunggal Inflasi di Indonesia - Mohamad Yusuf (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Transmission mechanism of monetary policy moves through various pathways, includingdirect monetary channel,interest ratechannel,credit channel, andexchange rate channel. This study used Vector Auto regression (VAR) model to analyze effectiveness of monetarypolicy transmission mechanism in Indonesia through the fourth channelperiod between 2000 first quarter to 2013 third quarter.This study used secondary data issued by BankIndonesia and BPS as well as from International Finance Statistic (IFS).The results showed that the interest rate channel isthemost effective compared with other pathways. The analysis is done through testing impulse response and variance decomposition tests illustrate the reliability of the use of the interest rate channel in reaching the end of the inflation target. Interest rates on the interbank money market is the most suitable variable is used as an operational target for the interest rate channel. Test results on path impulse response rate indicates that shocks RPUAB get a strong response and fast too.Keywords :transmission mechanismof monetary policy, inflation targeting, VAR analysis.